Predictors of the rate and course of reactive attachment disorder and disinhibited social engagement disorder symptoms in foster children during the first year of placement - Zimmermann, Janin; Kliewer-Neumann, Josephine; Bovenschen, Ina; Lang, Katrin; Gabler, Sandra; Nowacki, Katja; Spangler, Gottfried (Child Abuse & Neglect, 2024)
Background: Due to adverse care experiences, foster children are at risk for developing symptoms of reactive attachment disorder (RAD) and disinhibited social engagement disorder (DSED). Objective: This study investigated the factors influencing rate and course of RAD and DSED symptoms during the first year of placement in long-term foster care. Participants and setting: The sample consisted of 55 foster children aged 1 to 6 years. Measurements were taken at placement as well as 6 and 12 months after placement. Methods: RAD and DSED symptoms were assessed with the Disturbance of Attachment Interview (DAI). DSED symptoms were also assessed by observation with the Rating of Infant Stranger Engagement (RISE). Foster parents and caseworkers reported on children's preplacement experiences and placement characteristics. Results: RAD symptoms were rare at Wave 1 (5.5 %) and remitted in most children within the first six months of placement, t(54) = 3.06, p =.003. A total of 30.9 % of the foster children presented DSED symptoms according to the DAI, but only 5.5 % of the children according to the RISE. Foster parents reported symptom reduction, t(54) = 3.71, p =.003, while observational data indicated symptom stability. Prior placement in emergency foster care was associated with lower levels of RAD at Wave 1, F(1.62, 80.88) = 7.80, p =.002, while later placed children presented more RAD and DSED symptoms (RRAD2 = 0.07, RDSED2 = 0.08, RRISE2 = 0.12). Psychopathology of the biological parents (RRAD2 = 0.07, RDSED2 = 0.08) and visitation with the biological parents (RRISE2 = 0.14) predicted symptom stability. Conclusion: A substantial number of foster children present persistent DSED symptoms indicating a need for evidenced based interventions.
CRIS-Team Scopus Importer:2024-06-14
Keywords: Adverse childhood experiences; Disinhibited social engagement disorder; Foster children; Mental health; Neglect; Reactive attachment disorder